(untitled) (Jurnal Arsitektur ARCADE, 2026)
Tegal Old Town is a historic area that has played an important role in the development of the northern coastal region of Java, characterized by traditional and colonial buildings, historic street networks, and distinctive social activities. However, the existing delineation is still based primarily on geographical and administrative aspects, which do not fully represent the community’s perceptions, experiences, and meanings associated with the area. In addition, changes in building functions, deterioration of public spaces, and urban development have gradually diminished the area’s architectural character, historical value, and spatial experience. This study aims to identify the delineation of Tegal Old Town based on Sense of Place by integrating Place Identity, Place Attachment, and Place Dependence within the physical, social, and meaning dimensions. A Mixed Method Sequential Exploratory approach was employed through field observations, in-depth interviews, mental mapping, and a Likert-scale questionnaire involving 50 respondents. Data were analyzed using thematic analysis, descriptive statistics (mean score), triangulation, and spatial overlay. The findings show that Sense of Place-based delineation produces more contextual boundaries by integrating physical characteristics, social activities, and place meanings, providing a stronger basis for participatory and sustainable conservation and management of Tegal Old Town